2018
DOI: 10.21272/mmi.2018.4-11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of modernization of industrial sphere of industrial enterprise in accordance with requirements of the information economy

Abstract: In the paper is established that for the effective development of the industrial enterprise in the conditions of the information economy, should be the modernization of the production sphere of the enterprise. The main aim of the research to find out the optimal mechanism of modernization of industrial sphere in accordance with requirements of the information economy for the industrial enterprise development. To solve this problem, a mechanism for modernization of the industrial sphere of an industrial enterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 2 publications
1
42
0
5
Order By: Relevance
“…T. Yudina [10] presented a model of digital economy and a scheme of changing the structure of the world economy that is influenced by industrial revolutions. The peculiarity of the digital economy is its rapid development, in which every few years there are technologies that bring changes in the economy of almost all countries and change the universe [11,12,13,14,15,16]. The theoretical analysis of scientific sources [1,8,9,10] made it possible to conclude that when constructing buildings of different types and sizes, the sequence of the construction objects has an impact on total period of their construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…T. Yudina [10] presented a model of digital economy and a scheme of changing the structure of the world economy that is influenced by industrial revolutions. The peculiarity of the digital economy is its rapid development, in which every few years there are technologies that bring changes in the economy of almost all countries and change the universe [11,12,13,14,15,16]. The theoretical analysis of scientific sources [1,8,9,10] made it possible to conclude that when constructing buildings of different types and sizes, the sequence of the construction objects has an impact on total period of their construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, some group of the scientists [1][2][3] highlighted that in this process, the information gap and investment in education were the core elements of a sustainable business model. The scientists in the papers [4][5][6][7][8][9][10][11][12] proved that the investment and the financial system had a significant impact on the implementation of a sustainable business model and innovations. From the other point of views, the scientists in the papers [13][14][15][16][17] proved that key elements of a sustainable business model were ecological innovations and energy efficiency technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The scientists in the papers [46][47][48][49][50] demonstrated that corporate social responsibility influences the brand. The group of the scientists proved that an imbalance in financial sectors [51][52][53][54][55][56], green development [57][58][59][60][61][62][63][64][65][66][67], shadow economy and corruption [68][69][70][71][72][73][74][75], innovation technologies [67,[76][77][78][79][80][81][82][83] and a country's attractiveness [67,[82][83][84][85] influence the investment climate in the country and the company's image [86][87][88][89][90]…”
mentioning
confidence: 99%